Teach yourself visually Photoshop CS6 - Wooldridge, Mike; Stuart, Brianna (John Wiley & Sons, 2012)
Step-by-step screen shots show you how to tackle more than 160 Photoshop CS6 tasks. Each task-based spread covers a single technique, sure to help you get up and running on Photoshop CS6 in no time--Source other than Library of Congress